Competency As a Mediating Variable in The Effect of Job Training and Career Development on Employee Performance - Sumihar M. L. Tobing; Rosmegawati Rosmegawati; Wakhyudin Wakhyudin (School of Business, Bogor Agricultural University (SB-IPB), 2025)
Background: If a business consistently considers each team member's performance, it may keep expanding. Because a company's quality is the primary factor that determines its potential to succeed.Purpose: With competency serving as a moderating variable, this study intends to investigate how career growth and on-the-job training affect team member performance at PT. FIF Group Selong Branch.Design/methodology/approach: A questionnaire was given to each team member of the PT. FIF Group Selong Branch is gathering data. With 33 employees, the sample method employed a census sampling strategy. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to examine the data.Findings/Results: According to the study, career growth has no discernible impact on PT employees' performance, but job training and competency have a significant impact. FIF Organization. Competence can mitigate the impact of career growth and on-the-job training on PT employees' performance. FIF Group Selong BranchConclusion: This study serves as an assessment tool for organizational management, enabling workers to be creative in their work processes and encouraging them to try new things when completing tasks.Originality/value (State of the art): This study can serve as an assessment tool for management in the service industry, encouraging them to focus more on areas such as job training, team member career development, and competency in order to help the business achieve its goals as effectively as possible. Keywords: job training, career development, competency, employee performance, moderating variable